Thermal buckling measurement of a laminated composite plate under a uniform temperature distribution using the digital image correlation method. (May 2015) - Jin, Tailie; Ha, Ngoc San; Le, Vinh Tung; Goo, Nam Seo; Jeon, Ho Chan
Abstract: This paper presents the use of the Digital Image Correlation (DIC) technique to investigate the thermal buckling of a circular laminated composite plate subjected to a uniform distribution of temperature load. The circular laminated composite plate made of glass/epoxy was placed in a titanium ring without being fixed and the structure was heated from room temperature 30 °C to 120 °C in the heating chamber. The thermal deformation and strain of the composite plate resulting from the thermal load were measured using DIC. The buckling temperature and the first buckling mode shape were determined from the full-field deformation shape and temperature–displacement curve that were obtained from the experiment. In addition, the buckling temperature of the circular composite plate was also studied using energy theory. The results of the buckling temperature from DIC were close to the theoretical buckling temperature of the circular plate found using a simply supported boundary condition. In order to verify the proposed measurement method, the finite element analysis method was used to perform a nonlinear buckling analysis with the influence of imperfections. These results show that the present method is promising for studying thermal buckling of composite structures in diverse fields such as aerospace engineering.